Pathogenicity and virulence of Shigella sonnei: A highly drug-resistant pathogen of increasing prevalence - Xosé M. Matanza; Abigail Clements (Virulence)
Shigella spp. are the causative agent of shigellosis (or bacillary dysentery), a diarrhoeal disease characterized for the bacterial invasion of gut epithelial cells. Among the 4 species included in the genus, Shigella flexneri is principally responsible for the disease in the developing world while Shigella sonnei is the main causative agent in high-income countries. Remarkably, as more countries improve their socioeconomic conditions, we observe an increase in the relative prevalence of S. sonnei. To date, the reasons behind this change in aetiology depending on economic growth are not understood. S. flexneri has been widely used as a model to study the pathogenesis of the genus, but as more research data are collected, important discrepancies with S. sonnei have come to light. In comparison to S. flexneri, S. sonnei can be differentiated in numerous aspects; it presents a characteristic O-antigen identical to that of one serogroup of the environmental bacterium Plesiomonas shigelloides, a group 4 capsule, antibacterial mechanisms to outcompete and displace gut commensal bacteria, and a poorer adaptation to an intracellular lifestyle. In addition, the World Health Organization (WHO) have recognized the significant threat posed by antibiotic-resistant strains of S. sonnei, demanding new approaches. This review gathers knowledge on what is known about S. sonnei within the context of other Shigella spp. and aims to open the door for future research on understanding the increasing spread of this pathogen.